Novel temporin L antimicrobial peptides: promoting self-assembling by lipidic tags to tackle superbugs. (1st January 2020) - Bellavita, Rosa; Falanga, Annarita; Buommino, Elisabetta; Merlino, Francesco; Casciaro, Bruno; Cappiello, Floriana; Mangoni, Maria Luisa; Novellino, Ettore; Catania, Maria Rosaria; Paolillo, Rossella; Grieco, Paolo; Galdiero, Stefania
Abstract: The rapid development of antimicrobial resistance is pushing the search in the discovering of novel antimicrobial molecules to prevent and treat bacterial infections. Self-assembling antimicrobial peptides, as the lipidated peptides, are a novel and promising class of molecules capable of meeting this need. Based on previous work on Temporin L analogs, several new molecules lipidated at the N- or and the C-terminus were synthesised. Our goal is to improve membrane interactions through finely tuning self-assembly to reduce oligomerisation in aqueous solution and enhance self-assembly in bacterial membranes while reducing toxicity against human cells. The results here reported show that the length of the aliphatic moiety is a key factor to control target cell specificity and the oligomeric state of peptides either in aqueous solution or in a membrane-mimicking environment. The results of this study pave the way for the design of novel molecules with enhanced activities. Graphical Abstract: UF0001